2013
DOI: 10.1007/s10616-013-9668-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant activities with acute toxicity, cytotoxicity and mutagenicity of Cystoseira compressa (Esper) Gerloff & Nizamuddin from the coast of Urla (Izmir, Turkey)

Abstract: The aim of the study was to evaluate the biological activities with toxic properties of the methanol, hexane, and chloroform extracts of Cystoseira compressa (Esper) Gerloff & Nizamuddin from the Coast of Urla in the Aegean Sea. The extracts of C. compressa were tested for their antimicrobial and antioxidant activities in this study. Cytotoxic and mutagenic potentials of the extracts were also evaluated using cell culture and mutagenicity assays. Hexane extract was found to have higher total flavonoid and phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 44 publications
(40 reference statements)
2
26
2
Order By: Relevance
“…S. coronopifolius was collected in Berlengas, and as a natural reserve, this island presents(Mole & Sabale, 2013) a high biodiversity which results in high ecological pressures which can trigger the production of different compounds for protection.Regarding to the high scavenging activity presented by the supra-cited seaweeds, our results are in line with the ones obtained byZubia et al (2009), Wang et al (2009.Marine seaweed are exposed to intense light and high oxygen concentration leading to the formation of free radicals and other strong oxidizing agents(Mole et al, 2013;Shanab, Shalaby & El-Fayoumy, 2011). Therefore, in order to survive in this harsh environment, seaweeds also have protective enzymes and antioxidant molecules which can behave as reactive oxygen scavengersGüner et al, 2013;Munir, Sharif, Naz & Manzoor, 2013;Shanab et al, 2011).…”
supporting
confidence: 86%
“…S. coronopifolius was collected in Berlengas, and as a natural reserve, this island presents(Mole & Sabale, 2013) a high biodiversity which results in high ecological pressures which can trigger the production of different compounds for protection.Regarding to the high scavenging activity presented by the supra-cited seaweeds, our results are in line with the ones obtained byZubia et al (2009), Wang et al (2009.Marine seaweed are exposed to intense light and high oxygen concentration leading to the formation of free radicals and other strong oxidizing agents(Mole et al, 2013;Shanab, Shalaby & El-Fayoumy, 2011). Therefore, in order to survive in this harsh environment, seaweeds also have protective enzymes and antioxidant molecules which can behave as reactive oxygen scavengersGüner et al, 2013;Munir, Sharif, Naz & Manzoor, 2013;Shanab et al, 2011).…”
supporting
confidence: 86%
“…Antioxidants are known to act as pro-oxidants and inhibit cell viability via Fenton reaction (Dai and Mumper 2010) exhibiting anti-cancer properties. In our study extracts with (Murugan and Iyer 2013;Guner et al 2015), there are others claiming a protective role for those substances as cancer cells are known to require antioxidants for their survival Lee et al 2013;Mezghani et al 2013). Surely oxidative stress is one of the most common inducers of carcinogenesis (Valko et al 2006), however it is also known that once transformation is completed, cancer cells utilize antioxidant machinery to prevent further damage caused by reactive oxygen species (Saeidnia and Abdollahi 2013).…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, two other studies that used methanol extracts of C. bursa from Turkey or C. fragile from Britain were not able to find any toxicity on mammalian cancer cells [26,43]. Regarding the genus Cystoseira , several studies demonstrated cytotoxic effects on cancer cells from C. sedoides [24], C. myrica [41,46], and C. tamariscifolia [43], whereas C. compressa and C. sinuosa did not show toxic effects on human cancer cells [46,47]. Only very few studies exist on species of the genus Peyssonnelia .…”
Section: Discussionmentioning
confidence: 99%